2004
DOI: 10.1063/1.1811377
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the ratio of hardness to Young’s modulus on the friction and wear behavior of bilayer coatings

Abstract: Hardness and Young's modulus of high-quality cubic boron nitride films grown by chemical vapor deposition

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
54
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 169 publications
(57 citation statements)
references
References 20 publications
3
54
0
Order By: Relevance
“…Hardness (H) to Young modulus (E) ratio has been proposed as the key factor to measure the behaviour of wear resistance of bilayer coatings. It has been reported that the deformation around the indenter surface exhibit piling-up and sinking-in and the tendency of sinking-in increases with increasing H/E ratio [18]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…Hardness (H) to Young modulus (E) ratio has been proposed as the key factor to measure the behaviour of wear resistance of bilayer coatings. It has been reported that the deformation around the indenter surface exhibit piling-up and sinking-in and the tendency of sinking-in increases with increasing H/E ratio [18]. Fig.…”
Section: Mechanical Propertiesmentioning
confidence: 95%
“…Recent studies suggest that the ratio of hardness to elastic modulus (H/E) may be a more suitable parameter for predicting wear properties compared to evaluating hardness alone [27]. The effect of H/E on wear is based on the knowledge that materials with high H/E values are expected to have small accumulative strain and small accumulative strain energy in sliding, leading to high wear resistance [28]. Therefore, enhancing elasticity (i.e., to reduce E) may be a more suitable approach to improve wear resistance than enhancing the hardness of the material alone.…”
Section: Resultsmentioning
confidence: 98%
“…The datum of dentin (ζ = 0.264) locates in the region where steel (for GCr15 steel ζ = 0.287 in Figure 6) and Ti alloy (for Ti alloy ζ =0.230 in Figure 6 for enamel [3,4] , the ratios of r H E and ζ similar to steel and metallic glasses in dentin and enamel are very impressive. In fact, the ratio of r H E is related to the deformation properties of a rough surface to govern wear resistance in tribology [12] and the ratio of reversible work to total work ζ is the indication of energy dissipation. So, the relatively same position of enamel and metallic glasses in the diagram of r H E vs ζ (Figure 6) indicates that the enamel presents similar balanced functions in both the resistance against wearing and the energy dissipation as metals, rather than ceramics as people usually supposed.…”
Section: Resultsmentioning
confidence: 99%